2017
DOI: 10.1007/s13197-017-2849-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of fermented black tea juice with oolong tea infusion

Abstract: Fresh tea leaves were crushed into juice and then fermented (oxidation) to obtain fermented black tea juice, which can be used to prepare black tea beverage. The effects of addition of oolong tea infusion or tossing of tea leaves on the sensory quality and theaflavins (TFs) concentration of fermented black tea juice were investigated. The results showed that both addition of tea infusion and tossing of fresh tea leaves increased the TFs/thearubigins (TRs) ratio and improved the sensory quality of fermented bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is important to mention here, that during the COVID-19 pandemic of 2019–2020 the consumption of fermented food, especially beverages, increased in several countries [ 17 , 23 , 24 ]. In particular, the consumption of industrial kefir and kombucha increased [ 15 , 25 ] and the latter was reported, in the magazine Forbes, as the drink of 2020 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention here, that during the COVID-19 pandemic of 2019–2020 the consumption of fermented food, especially beverages, increased in several countries [ 17 , 23 , 24 ]. In particular, the consumption of industrial kefir and kombucha increased [ 15 , 25 ] and the latter was reported, in the magazine Forbes, as the drink of 2020 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The volatile chemical composition was investigated by the headspace solid-phase micro-extraction/gas chromatography-mass spectrometry (HS-SPME-GC-MS) ( 15 ). Before the extraction, the fiber of the SPME needle [50/30 μm divinylbenzene/carboxen/polydimethylsiloxane, StableFlex (2 cm), Product No.…”
Section: Methodsmentioning
confidence: 99%
“…Hawk tea is abundant in proteins, amino acids, sugars, polyphenols, and flavonoids, which are closely related to its physiological activity, and varies with the processing methods (Huang et al., 2016; Park, 2017; Xu, et al 2017; Xu, et al, 2016). It had been devoted more attention to the extraction and health benefits of flavonoids, polysaccharides, and essential oils from new hawk tea in recent years (Jia et al., 2014, 2017; Qin et al., 2018).…”
Section: Introductionmentioning
confidence: 99%